Intergenerational mobility in education: Estimates of the worldwide variation - Tharcisio Leone (United Nations Research Institute for Social Development (UNRISD), 2019)
This paper applies the recently published "Global Database on Intergenerational Mobility" to present a detailed picture of the chances of mobility around the world. The empirical results obtained from transition matrices and linear regression models, and based on harmonized data for education attainments of children and their parents from 148 countries, point to three main conclusions: first, the likelihood of attaining intergenerational mobility differs widely across countries and word regions; second, intergenerational persistence in education is particularly strong in the least-developed countries; and, finally - and perhaps most importantly - the mobility gap between poor and rich countries has increased over time.
Keywords: 330; Intergenerational mobility; inequality; education